The dark prophecy - Riordan, Rick (Riordan, Rick. Trials of Apollo, 2018)
In the second trial, Apollo/Lester must travel to the American Midwest in order to find the most dangerous Oracle before the second member of the evil Triumvirate does. Along the way Apollo will learn more about friendship as he travels with Calypso, Festus, and Leo.